Impact of New Media and Coffee Shop on the Lifestyle of Tarutung Youth - Entry Welny Sitindaon; Wensdy Sitindaon; Sandra Ronauli Sihombing; Nada Ratkovic (LPPM Universitas PGRI Sumatera Barat, 2023)
Individual activities in new media in much of the literature are considered separate and unrelated to the offline world. This research shows that activities in new media actually involve individual activities in everyday life. The popularity of coffee shop culture cannot become an urban culture without the role of new media. The presence of new media allows individuals or influencers to share photos and videos while in coffee shops. A coffee shop is also a good, aesthetic, contemporary object for all the services, food and drinks provided to consumers. This condition is what coffee shop consumers take advantage of to share their activities through new media. The aim of this research is to find out if activities in coffee shops are widely seen in new media by fellow users, friends and family, so that they attract a lot of interest from urban communities. This research uses qualitative methods and data collection techniques through in-depth interviews and field observations (coffee shops). The result of this research is that in the end each individual tries to produce interesting video and photo content in order to get comments, likes/dislikes in new media. Based on the results and discussion The presence of new media makes it possible for each user to be able to interact flexibly and produce content according to their abilities and wishes. The novelty of this research is that positive responses are a form of pride and happiness for those who post them on new media